Systemically dispersed innate IL-13–expressing cells in type 2 immunity - Price, April E. (National Academy of Sciences, 2010)
Type 2 immunity is a stereotyped host response to allergens and parasitic helminths that is sustained in large part by the cytokines IL-4 and IL-13. Recent advances have called attention to the contributions by innate cells in initiating adaptive immunity, including a novel lineage-negative population of cells that secretes IL-13 and IL-5 in response to the epithelial cytokines IL-25 and IL-33. Here, we use IL-4 and IL-13 reporter mice to track lineage-negative innate cells that arise during type 2 immunity or in response to IL-25 and IL-33 in vivo. Unexpectedly, lineage-negative IL-25 (and IL-33) responsive cells are widely distributed in tissues of the mouse and are particularly prevalent in mesenteric lymph nodes, spleen, and liver. These cells expand robustly in response to exogenous IL-25 or IL-33 and after infection with the helminth Nippostrongylus brasiliensis, and they are the major innate IL-13–expressing cells under these conditions. Activation of these cells using IL-25 is sufficient for worm clearance, even in the absence of adaptive immunity. Widely dispersed innate type 2 helper cells, which we designate Ih2 cells, play an integral role in type 2 immune responses.